2014
DOI: 10.1188/15.onf.44-51
|View full text |Cite
|
Sign up to set email alerts
|

Social Support, Self-Rated Health, and Lesbian, Gay, Bisexual, and Transgender Identity Disclosure to Cancer Care Providers

Abstract: Purpose/Objectives To describe factors related to diagnosis, identity disclosure, and social support among lesbian, gay, bisexual, and transgender (LGBT) patients with cancer, and to explore associations between these factors and self-rated health. Design Cross-sectional self-report survey design using descriptive and exploratory multivariate statistical approaches. Setting Online, Internet-based. Sample 291 LGBT patients (89% Caucasian; 50% gay, 36% lesbian, 7% bisexual, 3% transgender) with mixed cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
102
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(106 citation statements)
references
References 24 publications
1
102
0
1
Order By: Relevance
“…This process, often referred to as “coming out,” can be stressful, particularly in the context of cancer (Boehmer & Case, 2004). Given that cancer treatment requires socially intimate interactions with multiple new providers in new clinical settings, and that the beliefs of individual providers or the culture of a healthcare system may not be immediately apparent, sexual minority cancer patients must make a decision about coming out to each provider with whom they interact and may be concerned that their care will be compromised if a provider feels negatively about their sexual identity (Kamen, Smith-Stoner, Heckler, Flannery, & Margolies, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…This process, often referred to as “coming out,” can be stressful, particularly in the context of cancer (Boehmer & Case, 2004). Given that cancer treatment requires socially intimate interactions with multiple new providers in new clinical settings, and that the beliefs of individual providers or the culture of a healthcare system may not be immediately apparent, sexual minority cancer patients must make a decision about coming out to each provider with whom they interact and may be concerned that their care will be compromised if a provider feels negatively about their sexual identity (Kamen, Smith-Stoner, Heckler, Flannery, & Margolies, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of LGBQ patients in metropolitan areas revealed that approximately 70-80% of patients disclosed to providers (Durso & Meyer, 2013;Kamen et al, 2015). Alternatively, approximately 30% of patients avoid sexual orientation disclosure (Eliason & Schope, 2001;Petroll & Mosack, 2011).…”
Section: Patient-provider Communication and Sexual Orientation Disclomentioning
confidence: 95%
“…Recent research has documented the prevalence of sexual orientation disclosure to providers (e.g., Durso & Meyer, 2013;Kamen, Smith-Stoner, Heckler, Falnnery, & Margolies, 2015). However, similar to other disclosure contexts, little is known about how information management of the sexual orientation disclosure occurs (Afifi & Steuber, 2009;Mosack et al, 2013).…”
mentioning
confidence: 96%
“…[6][7][8] Stigmatizing encounters or fears of expected bias and mistreatment have resulted in a certain unwillingness to disclose sexual orientation in healthcare settings. [9][10][11][12] Non-disclosure for LGB adults may, consequently, have significant health and mental health risks. 6 A study conducted in the United States, for instance, demonstrated that non-disclosure among LGBs with cancer increased distress and negatively affected health outcomes and subsequent referrals to suitable care settings.…”
Section: Disclosure Of Sexual Orientation For Lgb Ayas In Healthcarementioning
confidence: 99%